Proceedings of the 9th Annual SIGCSE Conference on Innovation and Technology in Computer Science Education 2004
DOI: 10.1145/1007996.1008054
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing classroom lectures with digital sliding blackboards

Abstract: Traditional blackboard-based lectures provide context on the sliding blackboards. Modern lectures incorporating video projectors typically do not provide this context. We describe a project that combines both approaches to provide context for "modern" lectures. We also discuss the benefits for educators and students. The software is sufficiently versatile to incorporate practically any software for content display.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Focusing on the audience, Livenotes [11] supports students' cooperative note-taking overlaid on top of the instructors' slides. Other projects [4,23] support multiple projectors to enable information to persist longer, but require sophisticated infrastructure and are limited to showing previous slides on separate projectors, each slide filling an entire screen. Other classroom systems concentrated on capturing the lecture for later viewing.…”
Section: Presentation Systems Researchmentioning
confidence: 99%
“…Focusing on the audience, Livenotes [11] supports students' cooperative note-taking overlaid on top of the instructors' slides. Other projects [4,23] support multiple projectors to enable information to persist longer, but require sophisticated infrastructure and are limited to showing previous slides on separate projectors, each slide filling an entire screen. Other classroom systems concentrated on capturing the lecture for later viewing.…”
Section: Presentation Systems Researchmentioning
confidence: 99%
“…Some tools additionally provide a streaming feature in order to avoid having to download media files before presenting them. Other tools, such as virtual universities (e.g., VIROR [69,85]) or projects (e.g., Lecturnity [53] or Camtasia [83]), do roughly the same by providing the recording of lecture slide presentations together with annotations and sound recording.…”
Section: Handling Of Continuous Mediamentioning
confidence: 99%
“…Röüling et al [23] implemented a system that showed previous slides on different projectors during a presentation. The system also supported annotating materials and a separate view for the instructor.…”
Section: Presentation Systemsmentioning
confidence: 99%